2021
DOI: 10.7717/peerj.12276
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of a novel zinc finger protein-related gene-based prognostic model for breast cancer

Abstract: Background Breast invasive carcinoma (BRCA) is a commonly occurring malignant tumor. Zinc finger proteins (ZNFs) constitute the largest transcription factor family in the human genome and play a mechanistic role in many cancers’ development. The prognostic value of ZNFs has yet to be approached systematically for BRCA. Methods We analyzed the data of a training set from The Cancer Genome Atlas (TCGA) database and two validation cohort from GSE20685 and METABRIC datasets, composed of 3,231 BRCA patients. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…We also listed the other signatures that focus more on short-term survival, such as 1-year, 2-year, 3-year, and 5-year survival. We found our signature have similar short-term survival (3-year) prognostic value compared with them, such as the ferroptosis-related gene signature ( Wang et al, 2021a ; Wu et al, 2021a ; Zhu et al, 2021b ), pyroptosis-related gene signature ( Chen et al, 2022 ), necroptosis-related gene signature ( Yu et al, 2022 ), apoptosis-related gene signature ( Zou et al, 2022 ), zinc finger protein-related gene signature ( Ye et al, 2021 ), autophagy-related gene signature ( Lin et al, 2020 ), and metabolic-related gene signatures ( Lu et al, 2022b ). In addition, our model only involves four genes, while other models (11/13) tend to have more, which is more convenient to use to a certain extent.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…We also listed the other signatures that focus more on short-term survival, such as 1-year, 2-year, 3-year, and 5-year survival. We found our signature have similar short-term survival (3-year) prognostic value compared with them, such as the ferroptosis-related gene signature ( Wang et al, 2021a ; Wu et al, 2021a ; Zhu et al, 2021b ), pyroptosis-related gene signature ( Chen et al, 2022 ), necroptosis-related gene signature ( Yu et al, 2022 ), apoptosis-related gene signature ( Zou et al, 2022 ), zinc finger protein-related gene signature ( Ye et al, 2021 ), autophagy-related gene signature ( Lin et al, 2020 ), and metabolic-related gene signatures ( Lu et al, 2022b ). In addition, our model only involves four genes, while other models (11/13) tend to have more, which is more convenient to use to a certain extent.…”
Section: Resultsmentioning
confidence: 83%
“…To further explore the predictive ability of our signature, a comparison was performed among several significant molecular signatures employed for predicting OS in patients with BC. Compared with the other signature, such as ferroptosis, necroptosis, pyroptosis, and immune-related ( Lin et al, 2020 ; Zhong et al, 2020 ; Wang et al, 2021a ; Wu et al, 2021a ; Zhu et al, 2021b ; Ding et al, 2021 ; Ye et al, 2021 ; Lu et al, 2022a ; Lu et al, 2022b ; Chen et al, 2022 ; Chu et al, 2022 ; Yu et al, 2022 ; Zou et al, 2022 ), our signature indicated much higher AUCs, which indicated a better predictive ability, especially in predicting the long-term survival status. Furthermore, we constructed a prognostic nomogram that could simplify treatment decision-making for patients with BC.…”
Section: Discussionmentioning
confidence: 78%
“…Thus, high expression of MECOM is related to an increased risk of early death. Moreover, the higher the expression, the more advanced the stage of the disease [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been increasing evidence that KRAB-ZNFs promote tumor cell proliferation, invasion, and migration and help tumors evade the killing effects of host immune surveillance [ 7 , 8 ]. For example, multiple ZNF genes play key roles in the regulation of the tumor immune microenvironment (TME) in breast carcinoma, shortening the overall survival (OS) of patients [ 9 ]. Moreover, overexpression of ZNF655 promotes the proliferation and migration of glioma cells and inhibits apoptosis of cells by activating AURKA [ 10 ].…”
Section: Introductionmentioning
confidence: 99%